Development of perovskite in Pr substituted Pb(Zr0.52Ti0.48)O3and dielectric characteristic - N. Udomkan (2018)
The purpose of this research is to investigate the structure of lead zirconate titanate ceramics (Zr:Ti = 52:48) when doped with Pr2O3and the corresponding properties such as micro-structural properties, physical properties, dielectric constant (εr), piezo-electric properties (kp, Qm, and d33), and the ferroelectric property. The materials were prepared via conventional mixed oxide method and sintered at 1200°C. The Rietveld refinement of X-ray diffraction patterns and combination of both patterns revealed the tetragonal structure for all samples to have space group of P4mm. For higher dopant content (10 mol%), the pyrochlore phase of Pr2O3also appeared in the respective samples. These pyrochlore phases caused the detriment of dielectric and piezoelectric properties. For those with lower dopant content (1.00 mol%), the Pr ion substituted at the A and B sites with isovalent dopant effects, i.e. a lower value of εr, and kp. The hysteresis loops indicated the ferroelectric property for all samples. The microstructure showed dense grain according to a high density and the additional phases of Pr2O3were clearly observed for 10 mol% doping. The Curie temperature decreased with increasing dopant content, as determined from high temperature X-ray diffraction and differential scanning calorimetry. © World Scientific Publishing Company.